Consumption smoothing across space: Testing theories of risk-sharing in the ICRISAT study region of South India - Jonathan Morduch (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Panel data from villages in rural south India have been used for leading econometric studies on risk-sharing in village economies. The work has influenced debate on safety net design world-wide and has driven scholarly agendas on household economics. This paper critically surveys work to date and provides new results. The data show that state contingent transfers between households can in principle reduce total income risk by between 40 and 90 per cent. But risk-sharing with respect to total consumption is in practice quite imperfect, both at the village-level and within groups defined by caste and farm size. Taken together the results suggest that substitutes for formal credit markets function only moderately effectively, leaving substantial scope for remedial public action.
Keywords: D8; I3; O1; 330; consumption smoothing; risk sharing; informal insurance; India; Dorfwirtschaft; Verbraucherausgaben; Risiko; Indien (Süd)